5PSQ-003 Effectiveness of antiemetic therapy during chemotherapy in a regional hospital. (24th March 2020) - Salom, C; Galceran, MDLE; Serrais, J; Retamero, A; Parés, RM; Sànchez, X; Medina, M; Roch, MÁ; Ferràndez, D
Abstract : Background and importance: Chemotherapy induced nausea and vomiting (CINV) remains an important adverse effect as it affects the quality of life of patients, implies chemotherapy dose reductions and compromises adherence. Aim and objectives: To evaluate the effectiveness of antiemetic therapy in the control of CINV, comparing groups of patients with adequate and inadequate patterns, according to clinical practice guidelines. Material and methods: This was a longitudinal retrospective study for population characterisation and non-intervention. Patients receiving intravenous chemotherapeutic treatment from April to July 2018 were included. Independent variables: demographics (age and sex), and adequacy of the guidelines. Dependent variables: chemotherapy induced nausea (CIN), quantified by adding the scores obtained through a self-administered questionnaire based on the CTCAE scale, for the three phases (anticipated+acute+delayed); and chemotherapy induced vomiting (CIV), similarly quantified. Data are expressed as mean (SD) for continuous variables and absolute and relative frequency for categorical variables. Multivariable logistic regression models were used to study the association of adequacy and effectiveness. Statistical analyses were performed with the R software (V.3.4.3). A p value <0.05 was considered statistically significant. Results: A total of 797 chemotherapy cycles were administered to 148 patients during the study period. Of these, 133 patients aged 62.26 (11.13) years, 70 (52.63%) women, were included. They were divided into three groups, according to the adequacy of the guidelines: sufficient (75), excessive (38) and insufficient (20). The excess deviations (OR=0.311 (0.038, 1.535), p=0.197) or insufficient adequacy (OR=0.388 (0.057, 1.878), p=0.278) were not predictors of nausea. In contrast, insufficient adequacy was a predictor of vomiting (OR=17.907 (2.078, 290.042), p=0.015), while the excess deviation was not (OR=1.799 (0.064, 37.415), p=0.688). Conclusion and relevance: For all CINV anticipated, acute and delayed phases considered together, an insufficient antiemetic pattern was associated with worse control of vomiting, but not nausea. In future studies, separate assessment of the influence of the adequacy of the antiemetic pattern on each of the CINV phases deserves further investigation. References and/or acknowledgements: No conflict of interest.